Eksplorasi Fungsi Bahasa dalam Ritual Adat Suku Osing: Studi Pragmatik pada Anak Usia 5-7 Tahun - Lailiyah, Nur; Wijaya, Intan Prastihastari; Anisa, Salma Kurnia; Etikasari, Mutiara; Ghupti Nadia, Ingghar (Universitas Muhammadiyah Surabaya, 2025)
This study aims to explore the function of language in traditional rituals and 5-7 year olds' pragmatic understanding of language use. The study used a qualitative approach with communication ethnography method, involving participant observation and in-depth interviews of 20 children aged 5-7 years who participated in traditional rituals in the Osing tribal community, Banyuwangi. Data were collected through audio-visual recordings of children's interactions during traditional rituals, field notes, and interviews with children and traditional leaders. Data were analyzed using the pragmatics theoretical framework. The results showed that children were able to identify and interpret various language functions in traditional rituals, such as declarative (ritualistic), expressive (social identity), and directive (instructional and educational) functions. Children's understanding of pragmatics is reflected in their ability to respond appropriately to ritual expressions and adjust language use according to the customary context. The research findings also reveal the existence of a scaffolding process by adults in facilitating children's understanding of the pragmatic aspects of ritual language. This research contributes to a deeper understanding of the role of traditional rituals in early childhood pragmatic development and highlights the importance of preserving local wisdom as a rich source of language learning. The practical implications of this research include recommendations for integrating elements of indigenous rituals in early childhood education curricula to support the development of their pragmatic competence.